2012
DOI: 10.1002/cplu.201200134
|View full text |Cite
|
Sign up to set email alerts
|

A Yolk–Shell Fe3O4@C Composite as an Anode Material for High‐Rate Lithium Batteries

Abstract: Good egg: A unique yolk–shell Fe3O4@C composite with high loading ratio of 90 wt % has been prepared (see figure). As an anode material for lithium‐ion batteries, this composite exhibits a high capacity of 680 mAh g−1 even at a large current density of 5 A g−1, and makes it a promising anode material for next‐generation lithium‐ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…[160] With desirable free spaces for volume change accommodation, yolk@shell structures have also been fabricated to boost the electrochemical performances of Fe3O4. [162][163][164][165][166] Guan et al constructed…”
Section: Fe3o4-based 3d Nanostructuresmentioning
confidence: 99%
See 2 more Smart Citations
“…[160] With desirable free spaces for volume change accommodation, yolk@shell structures have also been fabricated to boost the electrochemical performances of Fe3O4. [162][163][164][165][166] Guan et al constructed…”
Section: Fe3o4-based 3d Nanostructuresmentioning
confidence: 99%
“…[162] Paik et al reported the synthesis of Fe3O4@C yolk-shell microcubes (Figure 10b) via an "etching-in-a-box" strategy. [165] The Fe3O4@C yolk-shell boxes with an optimized etching time of 2 h demonstrated the best anode performance in terms of specific capacity, cycling stability, and rate capability.…”
Section: Fe3o4-based 3d Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the synthesis techniques, a variety of scales and shapes can be synthesized, such as sphere, cube, prism, platelets, wire, rod, tube, etc. In order to synthesize Fe 3 O 4 @C core-shell nanostructures at different scales and shapes, several methodologies have been developed [34,37,[47][48][49][50][51][52][53][54][55].…”
Section: Synthesis Of Fe 3 O 4 @C Core-shell Nanoparticlesmentioning
confidence: 99%
“…So far, three main strategies have been widely used to improve the electrochemical performance of the transition metal oxide electrodes [22][23][24]: (I) Construction of mesoporous nanostructures, such as nanoparticles (NPs) [25], nanospheres [26], nanotubes [27] and nanosheets [28], in order to keep the absolute small volume changes and stabilize the dimensional integrity and the microstructure of the overall material during cycling. For example, Liu et al [29] synthesized the amorphous SnO2 nano-membranes as anodes for LIBs, which demonstrated a long cycling life of 1000 cycles at 1600 mA g −1 with a high reversible capacity of 854 mAh g −1 .…”
Section: Introductionmentioning
confidence: 99%